INVENTARISASI TUMBUHAN BAWAH DI AREAL PROGRAM STUDI PENGELOLAAN HUTAN POLITEKNIK PERTANIAN NEGERI SAMARINDA - Agustina Murniyati; Indri Mayuni (JURNAL AGRIMENT, 2021)
The understorey functions as a ground cover that maintains moisture so that the rapid decompositionprocess can provide nutrients for the main crop the nutrient cycle can take place perfectly, theavalanches that fall as litter will be returned to the tree in the form of nutrients which, as is known, willbe broken down by bacteria and microbes. This study aims to determine the type, number, andpresence of each understorey in the area of the Samarinda State Agricultural Polytechnic ForestManagement Study Program, precisely behind the Silviculture Laboratory. The research method useda single plot measuring 60 m x 32 m with sub plots measuring 2 m x 2 m which were arrangedsystematically so that there were 480 sub plots.The results of the study found as many as 23 speciesof understorey which were included in 22 genera, 18 families, as many as 14.616 individuals, in1.528 attendances. The most common species found were Asystasia intrusa as many as 5.728individuals with distribution in 304 plots, then Clidemia hirta (L.) D.Don with 1.864 plants withdistribution in 240 plots and Stenochlaena palutris (Burm.f.) Bedd species. as many as 1.344 with adistribution of 56 plots. While the types of Alpina sp and Imperata chylindrica as many as 8 plant in 8plot.